Phenotypic plasticity underlies seasonal and latitudinal variation in thermal tolerance in a native bee - Matt C. Elmer; Keyne Monro; Harley Thompson; Aidan Stuckey; Vanessa Kellermann (Ecology, 2025)
Climate change threatens biodiversity and ecosystem services around the globe. Despite the importance of native bees as pollinators, there is evidence of global declines, and we know very little about how climate shapes their distributions now and into the future. In the current study, we combined large‐scale seasonal field sampling and experimental acclimation to examine whether populations of an Australian bee, Exoneura robusta , vary in their capacity to adapt to different climates. Collecting female bees across a latitudinal cline and examining heat and cold tolerance, we found populations did not vary in their heat tolerance along a latitudinal gradient. In contrast, bees from higher latitudes tended to be more cold‐tolerant than bees from lower latitudes, but the relationship between cold tolerance and latitude differed between summer and spring (post‐winter). Such seasonal variation suggests that phenotypic plasticity plays a role in shaping cold tolerance, as bees are likely to belong to the same generation from summer to spring. To untangle the roles of plasticity and genetic variation in shaping variation in thermal tolerance across seasons, we acclimated adult females from three populations spanning the species' distributional range to either 21 or 26°C in glasshouses (approximating summer and spring/autumn temperatures experienced throughout their range). We then estimated heat and cold tolerance. Contrasting acclimation responses observed in the glasshouses to those observed in the field point to phenotypic plasticity in cold tolerance rather than genetic variation underpinning population variation. In contrast, heat tolerance varied little in the field and in our glasshouse experiments. These results suggest bees may have little capacity to increase their heat tolerance, which is high at ~47°C, via genetic or plastic responses as climate changes.

Exome-informed formulations of food proteins enhance body growth and feed conversion efficiency in ad libitum-fed mice - Tong Wu; Davaatseren Baatar; Anne E. O' Connor; Moira K. O'Bryan; Jessica M. Stringer; Karla J. Hutt; Minoli Malimige Aponso; Keyne Monro; Jiaqiang Luo; Yingchun Zhu; Andreas Ernst; Elyse O.K. Swindells; et al. (Food Research International, 2024)

Climate adaptation and vulnerability of foundation species in a global change hotspot - Cristóbal Gallegos; Kathryn A. Hodgins; Keyne Monro (Molecular Ecology, 2023)
Climate change is altering species ranges, and relative abundances within ranges, as populations become differentially adapted and vulnerable to the climates they face. Understanding present species ranges, whether species harbour and exchange adaptive variants, and how variants are distributed across landscapes undergoing rapid change, is therefore crucial to predicting responses to future climates and informing conservation strategies. Such insights are nonetheless lacking for most species of conservation concern. We assess genomic patterns of neutral variation, climate adaptation and climate vulnerability (offsets in predicted distributions of putatively adaptive variants across present and future landscapes) for sister foundation species, the marine tubeworms Galeolaria caespitosa and Galeolaria gemineoa , in a sentinel region for climate change impacts. We find that species are genetically isolated despite uncovering sympatry in their ranges, show parallel and nonparallel signals of thermal adaptation on spatial scales smaller than gene flow across their ranges, and are predicted to face different risks of maladaptation under future temperatures across their ranges. Our findings have implications for understanding local adaptation in the face of gene flow, and generate spatially explicit predictions for climatic disruption of adaptation and species distributions in coastal ecosystems that could guide experimental validation and conservation planning.

Correlational selection on size and development time is inconsistent across early life stages - Evatt Chirgwin; Keyne Monro (Evolutionary Ecology, 2020)

Should mothers provision their offspring equally? A manipulative field test - Hayley Cameron; Keyne Monro; Dustin J. Marshall (Ecology Letters, 2017)
Within‐brood variation in offspring size is universal, but its causes are unclear. Theoretical explanations for within‐brood variation commonly invoke bet‐hedging, although alternatives consider the role of sibling competition. Despite abundant theory, empirical manipulations of within‐brood variation in offspring size are rare. Using a field experiment, we investigate the consequences of unequal maternal provisioning for both maternal and offspring fitness in a marine invertebrate. We create experimental broods of siblings with identical mean, but different variance, in offspring size, and different sibling densities. Overall, more‐variable broods had higher mean performance than less‐variable broods, suggesting benefits of unequal provisioning that arise independently of bet‐hedging. Complementarity effects drove these benefits, apparently because offspring‐size variation promotes resource partitioning. We suggest that when siblings compete for the same resources, and offspring size affects niche usage, the production of more‐variable broods can provide greater fitness returns given the same maternal investment; a process unanticipated by the current theory.

Limited evolutionary responses to harvesting regime in the intensive production of algae - Rebecca J Lawton; Nicholas A Paul; Dustin J. Marshall; Keyne Monro (Journal of Applied Phycology, 2017)

Why do larger mothers produce larger offspring? A test of classic theory - Hayley Cameron; Keyne Monro; Martino Malerba; Stephan Munch; Dustin Marshall (Ecology, 2016)
Across a wide range of taxa, larger mothers produce larger offspring. Theory assumes that larger, more fecund mothers create higher local densities of siblings, and so larger mothers produce larger offspring to offset sibling competition. This assumption has been debated for over 30 yr, but direct empirical tests are surprisingly rare. Here, we test two key assumptions of classic theories that predict sibling competition drives maternal‐size–offspring‐size ( MSOS ) correlations: (1) independent effects of offspring size and sibling density on offspring performance or (2) as a product of an interaction between these two factors. To simultaneously test these alternative assumptions, we manipulate offspring size and sibling density in the marine invertebrate, Bugula neritina, and monitor offspring performance in the field. We found that depending on the fitness metric being considered, offspring size and sibling density can either independently or interactively affect offspring performance. Yet sibling density did not affect offspring performance in the ways that classic theories assume. Given our results, it is unlikely that sibling competition drives the positive MSOS correlation observed in this species. Empirical support for these classic theories remains lacking, suggesting alternative explanations are necessary.

The biogeography of fertilization mode in the sea - Keyne Monro; Dustin J. Marshall (Global Ecology and Biogeography, 2015)
Aim Knowledge of the biogeography of life histories is central to understanding and predicting the impacts of global change on key functional traits that shape species distributions and transcend taxonomic boundaries. Whether species are internal or external fertilizers is a fundamental aspect of reproductive diversity in the sea, and has profound ecological and evolutionary consequences. However, geographic variation in this trait and the factors that potentially drive it (e.g. transitions in associated life‐history traits, ecological conditions that favour one mode over the other or the evolutionary history of species) remain poorly characterized. Location Oceans world‐wide. Methods We collated life‐history data (modes of fertilization and development), geographic data and biophysical data (sea‐surface temperatures and food availability) for 1532 marine species spanning 17 invertebrate phyla. We used standard and phylogenetic logistic regressions to evaluate latitudinal gradients in fertilization mode, plus their interactions with development (transitions from planktonic to aplanktonic development, or from feeding to non‐feeding larvae) and taxonomy. We also explored the dependence of fertilization mode on biophysical variables to understand how ecology potentially contributes to geographic variation in this trait. Results Fertilization mode often varies predictably with latitude, but the exact nature of this relationship depends on developmental mode and the phylum under consideration. Some commonalities were evident, however, with the likelihood of internal fertilization declining at higher latitudes for A nnelida and E chinodermata with aplanktonic development, but increasing at higher latitudes for C nidaria and Porifera with non‐feeding, planktonic larvae. Synergistic effects of temperature and food availability may potentially shape some of these patterns. Main conclusions There are latitudinal gradients in fertilization mode in the sea. The variation among phyla and developmental modes, however, is a complexity that is unexplained by existing theory. Combined effects of recent adaptation and deeper phylogenetic history have probably shaped this systematic variation in the reproductive ecology of marine organisms.

Revealing hidden evolutionary capacity to cope with global change - Evatt Chirgwin; Keyne Monro; Carla M. Sgro; Dustin J. Marshall (Global Change Biology, 2015)
The extent to which global change will impact the long‐term persistence of species depends on their evolutionary potential to adapt to future conditions. While the number of studies that estimate the standing levels of adaptive genetic variation in populations under predicted global change scenarios is growing all the time, few studies have considered multiple environments simultaneously and even fewer have considered evolutionary potential in multivariate context. Because conditions will not be constant, adaptation to climate change is fundamentally a multivariate process so viewing genetic variances and covariances over multivariate space will always be more informative than relying on bivariate genetic correlations between traits. A multivariate approach to understanding the evolutionary capacity to cope with global change is necessary to avoid misestimating adaptive genetic variation in the dimensions in which selection will act. We assessed the evolutionary capacity of the larval stage of the marine polychaete Galeolaria caespitosa to adapt to warmer water temperatures. Galeolaria is an important habitat‐forming species in Australia, and its earlier life‐history stages tend to be more susceptible to stress. We used a powerful quantitative genetics design that assessed the impacts of three temperatures on subsequent survival across over 30 000 embryos across 204 unique families. We found adaptive genetic variation in the two cooler temperatures in our study, but none in the warmest temperature. Based on these results, we would have concluded that this species has very little capacity to evolve to the warmest temperature. However, when we explored genetic variation in multivariate space, we found evidence that larval survival has the potential to evolve even in the warmest temperatures via correlated responses to selection across thermal environments. Future studies should take a multivariate approach to estimating evolutionary capacity to cope with global change lest they misestimate a species’ true adaptive potential.

Predicting evolutionary responses to climate change in the sea - Philip L. Munday; Robert R. Warner; Keyne Monro; John M. Pandolfi; Dustin J. Marshall (Ecology Letters, 2013)
An increasing number of short‐term experimental studies show significant effects of projected ocean warming and ocean acidification on the performance on marine organisms. Yet, it remains unclear if we can reliably predict the impact of climate change on marine populations and ecosystems, because we lack sufficient understanding of the capacity for marine organisms to adapt to rapid climate change. In this review, we emphasise why an evolutionary perspective is crucial to understanding climate change impacts in the sea and examine the approaches that may be useful for addressing this challenge. We first consider what the geological record and present‐day analogues of future climate conditions can tell us about the potential for adaptation to climate change. We also examine evidence that phenotypic plasticity may assist marine species to persist in a rapidly changing climate. We then outline the various experimental approaches that can be used to estimate evolutionary potential, focusing on molecular tools, quantitative genetics, and experimental evolution, and we describe the benefits of combining different approaches to gain a deeper understanding of evolutionary potential. Our goal is to provide a platform for future research addressing the evolutionary potential for marine organisms to cope with climate change.

Invasive ecosystem engineer selects for different phenotypes of an associated native species - Jeffrey T. Wright; Paul E. Gribben; James E. Byers; Keyne Monro (Ecology, 2012)
Invasive habitat‐forming ecosystem engineers modify the abiotic environment and thus represent a major perturbation to many ecosystems. Because native species often persist in these invaded habitats but have no shared history with the ecosystem engineer, the engineer may impose novel selective pressure on native species. In this study, we used a phenotypic selection framework to determine whether an invasive habitat‐forming ecosystem engineer (the seaweed Caulerpa taxifolia ) selects for different phenotypes of a common co‐occurring native species (the bivalve Anadara trapezia ). Compared to unvegetated habitat, Caulerpa habitat has lower water flow, lower dissolved oxygen, and sediments are more silty and anoxic. We determined the performance consequences of variation in key functional traits that may be affected by these abiotic changes (shell morphology, gill mass, and palp mass) for Anadara transplanted into Caulerpa and unvegetated habitat. Both linear and nonlinear performance gradients in Anadara differed between habitats, and these gradients were stronger in Caulerpa compared to unvegetated sediment. Moreover, in Caulerpa alternate phenotypes performed well, and these phenotypes were different from the dominant phenotype in unvegetated sediment. By demonstrating that phenotype–performance gradients differ between habitats, we have highlighted a role for Caulerpa as an agent of selection on native species.

Multivariate selection shapes environment-dependent variation in the clonal morphology of a red seaweed - Keyne Monro; Alistair G. B. Poore; Robert Brooks (Evolutionary Ecology, 2007)